PERBANDINGAN HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X IIS PEMINATAN DENGAN KELAS X MIPA LINTAS MINAT DI SMA NEGERI 15 PEKANBARU - Ningrum Fadhillah; Suarman Suarman; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the comparison of economic learning outcomes for student Class X IIS (Specialization) with student Class X MIPA (Cross Interest) in SMA Negeri 15 Pekanbaru in 2018/ 2019 school year. The population was all student Class X IIS (Specialization) and student Class X MIPA (Cross Interest) who took lesson in economic intersest where data was examined by means of documentation and questionnaires.The data analysis technique used is path analysis by using SPSS (Stastical Package for Social Science) program. The results showed that: (1) There was difference between the economic learning outcomes of student Class X IIS (Specialization) and student Class X MIPA (Cross Interest). (2) There are differences in the level of factors that affect learning outcomes. The learning outcomes of class X IIS (Specialization) are better than the results of economic learning in Class X MIPA (Cross Interest) students.Key Words: Learning Outcomes, Specialization, Cross Interest